2018
DOI: 10.1371/journal.ppat.1006916
|View full text |Cite
|
Sign up to set email alerts
|

Infection with hepatitis C virus depends on TACSTD2, a regulator of claudin-1 and occludin highly downregulated in hepatocellular carcinoma

Abstract: Entry of hepatitis C virus (HCV) into hepatocytes is a complex process that involves numerous cellular factors, including the scavenger receptor class B type 1 (SR-B1), the tetraspanin CD81, and the tight junction (TJ) proteins claudin-1 (CLDN1) and occludin (OCLN). Despite expression of all known HCV-entry factors, in vitro models based on hepatoma cell lines do not fully reproduce the in vivo susceptibility of liver cells to primary HCV isolates, implying the existence of additional host factors which are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 66 publications
1
29
1
Order By: Relevance
“…Indeed, OCLN is known to traffic through the basolateral membrane towards TJs133 and its subcellular localisation appears to be dependent on its phosphorylation status: phosphorylated forms of OCLN mainly are found in TJs of epithelial cells, while less phosphorylated forms are localised at the basolateral membrane and in the cytosol 134. This is in line with a recent report showing that tumour-associated calcium signal transducer 2 (TACSTD2) regulates HCV entry by leading to the phosphorylation of CLDN1 and OCLN and regulates their subcellular localisation 135. The importance of the subcellular localisation of OCLN for HCV entry is also underscored by the fact that only OCLN and its splice variant OCLN-ex7ext that both localise to the plasma membrane are able to promote HCV entry in contrast to other OCLN splice variants that exhibit an intracellular localisation 136.…”
Section: Tj Proteins and The Gi Tractsupporting
confidence: 92%
“…Indeed, OCLN is known to traffic through the basolateral membrane towards TJs133 and its subcellular localisation appears to be dependent on its phosphorylation status: phosphorylated forms of OCLN mainly are found in TJs of epithelial cells, while less phosphorylated forms are localised at the basolateral membrane and in the cytosol 134. This is in line with a recent report showing that tumour-associated calcium signal transducer 2 (TACSTD2) regulates HCV entry by leading to the phosphorylation of CLDN1 and OCLN and regulates their subcellular localisation 135. The importance of the subcellular localisation of OCLN for HCV entry is also underscored by the fact that only OCLN and its splice variant OCLN-ex7ext that both localise to the plasma membrane are able to promote HCV entry in contrast to other OCLN splice variants that exhibit an intracellular localisation 136.…”
Section: Tj Proteins and The Gi Tractsupporting
confidence: 92%
“…Pathway analysis from KEGG and Panther demonstrated that tight junction and Wnt signaling pathway are among the most relevant pathways for HCC. Tight junction signaling contributes to pathogenesis of GC and CRC, plays functional roles in epithelial-to-mesenchymal transition and viral entry, and could be used as potential targets for gastrointestinal and liver disease; while Wnt signaling pathway is well known to impact on hepatocarcinogenesis and HCC progression [42][43][44][45]. These results suggested that these DECs may participate in HCC progression by regulating their parental genes.…”
Section: Discussionmentioning
confidence: 94%
“…Regression analysis showed that Tacstd-2 concentrations may affect patients hemoglobin levels. Sekhar et al [18] investigated the relationship between the tacstd-2 molecule and hepatocellular carcinoma due to Hep C. They reported that both Hep C virus cellular infection and viral replication rates were decreased in cells with increased tacstd-2 expression in patients with hepatocellular carcinoma. In our study, there were only three patients with hepatocellular carcinoma thus we did not attempt separate statistical analysis for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tacstd-2 binds directly to claudin 1 and 7 and is required for these proteins to act as carriers to the cell membrane or to localize to the plasma membrane without degradation by the ubiquitin proteasome system [18]. Tacstd-2 has an effect on the expression of Occludin and Claudin, which play a role in the entry of Hep C virus into the cell.…”
Section: Introductionmentioning
confidence: 99%